The Design Process of Defect Detection Method for Large Industrial Automatic Control Software - Wang, Zhen Chao (Applied Mechanics and Materials, 2014)
The current difference trend of automatic control software structure is more obvious, software integration makes linking correlation of overall structure appeared to play down. No significant linking characteristics exist between structural ports. The traditional detection methods of software defect are utilized to locate software defect under the differentiation structural framework, due to the lack of clear articulation feature to indicate the location region, resulting in unidentified area which software defect signal belong to and position deviation. In this paper, software defect detection method was proposed on the basis of difference structure fusion algorithm. The signal fusion technology was applied to mix the signal of software defect detection effectively, and chaos particle swarm algorithm optimization was employed to support vector machine parameters, establish the optimal models of software defect prediction, thus completing the software defect detection. Experimental results show that the algorithm for software defect detection, can greatly improve the accuracy of detection.